Mongolia Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2018)
Notwithstanding its long-term achievements, Mongolia now experiences three main problems: unstable economic growth, population wellbeing at risk and growing environmental stress. The Systematic Country Diagnostic gives a general analysis of the main problems of the Mongolian economy and its general causes and, in addition, proposes a list of development priorities for the country.